A Highly Precise On-State Voltage Measurement Circuit With Dual Current Sources for Online Operation of SiC MOSFETs - Hui Meng; Letian Xiang; Luwei Zuo; Fujun Zheng; Ze Zhou; Jianlong Kang; Zhen Xin; Haoze Luo (IEEE Open Journal of Power Electronics, 2023)
This letter proposes an on-state drain-source voltage ( ${V}_{{\rm{ds,on}}}$ ) measurement circuit for SiC MOSFETs. The proposed circuit effectively solves the problem of inconsistent diode volt-ampere characteristics through an additional current source. The voltage difference between the two diodes is compensated by adjusting the auxiliary current under the condition of a fixed first current. This circuit does not require diode pre-selection and significantly improves measurement accuracy. The circuit is implemented in a double-pulse test (DPT) of a SiC MOSFET (900 V/23 A, 25 °C). The results show that the circuit has a fast response speed with a delay time of 0.4 μs. Even at the same current, the forward voltage difference between the two diodes reaches 3.32 mV. Compared to measurement results from a six-bit semi-digital multimeter, the measurement error of the proposed circuit is less than 1.5% at different currents and temperatures.